Progress on numerical model development of 1D debris flow using Langrangian Galerkin Method - Rahardjo, Adam Pamudji (2013)
The Lagrangian Finite Element Galerkin Method is implemented for modeling ID debris flow model. This approach is expected will provide better simulation result for the fast moving abrupt front modeling than that of the most of Eulerian based numerical methods that face difficulties in handling phase elTor of higher frequency components. Semi two-phase flow equations for debris flow model are adopted. There are two conservation of mass equations that are for the mixture and for the solid phase. However, there is only one equation for momentum conservation. The Galerkin formulation is applied for the matrix-vector form equations. Issues on numerical stability and boundary treatment are discussed. The current progress shows promising results for the expected improvement of the debris flow model performance.